PENANAMAN NILAI KARAKTER MELALUI PROGRAM TAHFIZ AL-QUR’AN SISWA KELAS VII MTs AL-KHAIRIYAH KECAMATAN BANTAN KABUPATEN BENGKALIS - Norhayati, Siti; Robiah, Robiah (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research carries the title of Character Value Cultivation through the Tahfiz Al-Qur'an Program for Class VII MTs Al-Khairiyah Students, Bantan District, Bengkalis Regency. This research aims to instill good character for the development of life in the future. The reason why researchers choose this title is how to instill character values in grade VII MTs students through the Qur'an tahfiz program. While the formulation of the problem is how teachers instill character values through the tahfiz al-qur'an program for grade VII MTs Al-Khairiyah students, Bantan District, Bengkalis Regency and what character values can be taken from students through the tahfiz al-qur'an program for grade VII MTs Al-Khairiyah students, Bantan District, Bengkalis Regency. Data collection techniques with several techniques, namely data collection techniques using observation, interviews, documentation. In analyzing data using qualitative descriptive methods. The results of research on instilling character values provide good examples or examples, through habituation of motivation to children and good communication and being honest and open